Surface Antigen 1 Is a Crucial Secreted Protein That Mediates Babesia microti Invasion Into Host Cells - Li, Muxiao; Ao, Yangsiqi; Guo, Jiaying; Nie, Zheng; Liu, Qin; Yu, Long; Luo, Xiaoying; Zhan, Xueyan; Zhao, Yangnan; Wang, Sen; An, Xiaomeng; He, Lan; et al. (Frontiers in Microbiology, 2020)
Babesia microti, a tick-borne intraerythrocytic zoonotic protozoan, causes most of human babesiosis in the world, and patients usually experience intermittent fever, fatigue, and chills, followed by a combination of additional symptoms and even death in severe cases. Unfortunately, there is no curable drug or effective vaccine available, and the mechanism of related virulence factors in invasion to host cells during the merozoite stage is unclear. Here, we evaluated a secreted protein annotated as B. microti surface antigen 1 (BmSA1) and identified from in vitro culture supernatant by liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS). BmSA1 fragment was expressed in E. coli to prepare polyclonal antiserum. Western blot analysis revealed the existence of BmSA1 in the lysate of the parasites and the hemolysate of infected red blood cells (iRBCs). Laser confocal microscopy confirmed BmSA1 as a secreted protein with diffuse distribution around the parasites in red blood cells (RBCs). The adhesion capacity of BmSA1 against the host RBCs was tested by RBC binding assays using the recombinant BmSA1 protein (rBmSA1), which was shown to specifically bind to host RBCs. Further in vitro antiserum-neutralization test demonstrated that the growth of parasites could be significantly inhibited by the anti-BmSA1 antiserum. These results indicate that BmSA1 is a crucial factor for B. microti invasion into host RBCs with an important role in host-parasite interactions during the merozoite stage and has the potential use as a vaccine candidate due to its high secretion amount.